Triboelectric nanogenerator with double rocker structure design for ultra-low-frequency wave full-stroke energy harvesting. (July 2021) - Yang, Yanfei; Yu, Xin; Meng, Lixia; Li, Xiang; Xu, Yuhong; Cheng, Tinghai; Liu, Shiming; Wang, Zhong Lin
Abstract: The triboelectric nanogenerator (TENG) is a unique revolutionary technology for harvesting energy from the environment and transforming that energy into electricity. The present paper proposes a double rocker triboelectric nanogenerator (DR-TENG), which is used to harvest energy from intermittent reciprocating motions and ultimately obtain electric energy in a controllable manner. The DR-TENG comprises a mechanical transmission structure, generation unit, and shell. The mechanical energy harvested by the pendulum rod is stored in a spiral spring via the mechanical transmission structure, and the energy is then transformed into controllable electric energy through a switching structure and generation unit. The experimental results show that the open-circuit voltage of the DR-TENG is 450 V, the short-circuit current is 36 μ A, and the peak power is 11 mW. In a water-wave simulation experiment, the DR-TENG powered 400 LEDs in series and a commercial thermometer with a bridge rectifier. This paper provides an effective method for the harvesting of irregular full-stroke energy in an ultra-low-frequency environment. Graphical abstract: Highlights: A double rocker triboelectric nanogenerator (DR-TENG) is proposed to harvest full-stroke energy. Random mechanical energy is harvested and converted into regular electrical energy by mechanical method. The DR-TENG lights up 400 LEDs and powers a thermometer, demonstrating the potential application in energy harvesting.